Vibrational response of elastic membranes coupled to acoustic fluids using a BEM–BEM formulation (2014)
In the last two decades, few works have been reported in the literature related to analysis of fluid–structure interaction problems using Boundary Element Method for modeling both structure and fluid. To the author’s knowledge, none of them applied to the dynamic analysis of elastic membranes coupled to acoustic fluids. In this work a full time-direct Boundary Element Formulation for the dynamic analysis of elastic membranes coupled to acoustics fluid is presented. The elastic membranes is modeled using the classical linear elastic pre-stretched membrane theory. The acoustic fluid is modeled using the acoustic-wave equation for homogeneous, isotropic, inviscid and irrotational fluids. Elastostatic fundamental solution is used in the boundary element formulation for the elastic membrane. The boundary element formulation for the acoustic fluid is based on the fundamental solution of three dimensional Poisson equation. Domain integrals related to inertial terms and those related with distributed pressure on membrane, were treated using the Dual Reciprocity Boundary ElementMethod. Fluid–structure coupling equations were established considering the continuity of the normal acceleration of the particles and dynamic pressure at fluid–structure interfaces. The time integration is carried out using the Houbolt method. Results obtained shows the accuracy and efficiency of the proposed boundary element formulation. © The Society for Experimental Mechanics, Inc. 2014.